2009
DOI: 10.5194/aab-52-410-2009
|View full text |Cite
|
Sign up to set email alerts
|

The content of chosen chemical elements in wool of sheep of different origins and breeds

Abstract: Abstract. The following chemical elements in sheep wool originating from Poland (Polish Mountain Sheep), Greece (Karagounico breed), and Syria (Awassi breed) were analysed: macroelements (Ca, P, Na, K, Mg, S), trace elements (Al, Ba, Co, Cu, Fe, Mn, Mo, Sr, Ti, Zn) and heavy metals (As, Cd Hg, Pb). Some statistically significant differences were observed between the content of the examined elements in sheep wool collected in the above countries. Sulphur, calcium, sodium and potassium were found in the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 11 publications
4
24
2
Order By: Relevance
“…This element had the highest variability. Patkowska-Sokola et al (2009) reported the range of 3.4 to 22.9 mg/kg DM in sheep wool; a similar range of 3.8-20.0 mg/kg DM was found by CyganSzczegielniak et al (2014) for Mn concentrations in cow hair, which corresponds with our mean result. Roug et al (2015) report a Mn concentration of 0.02-120.0 mg/kg DM in mule deer hair.…”
Section: Manganesesupporting
confidence: 93%
“…This element had the highest variability. Patkowska-Sokola et al (2009) reported the range of 3.4 to 22.9 mg/kg DM in sheep wool; a similar range of 3.8-20.0 mg/kg DM was found by CyganSzczegielniak et al (2014) for Mn concentrations in cow hair, which corresponds with our mean result. Roug et al (2015) report a Mn concentration of 0.02-120.0 mg/kg DM in mule deer hair.…”
Section: Manganesesupporting
confidence: 93%
“…the manner of nutrition, the degree of environmental pollution, etc. (4,9,(17)(18)(19). This fact may explain the observed variability in the content of chemical elements in the hair coat of dachshunds.…”
Section: Discussionmentioning
confidence: 94%
“…For a very long time, the hair of mammals have been used by humans for production of various kinds of everyday use objects and for industrial purposes. They are, however, also a valuable research material supplying the information on health status of an animal, excess or shortage of various elements in an organism, and, moreover, the perfect bioindicator of environment pollution (4,9,18). Results of the studies concerning hair coat contribute to more detailed knowledge of mammals.…”
mentioning
confidence: 99%
“…In the case of sheep in Poland various values are given, i.e. from 4.34 to 7.23 mg/kg depending on the state of the environment (Patkowska-Sokoła et al 2009), while in Suffolk and Rambouillet breeds in Mexico as much as 1.72-2.16 mg/kg (Ramirez-Perez et al 2000). Large differences are also observed in other animals, for example in hair of horses in Poland the content was 0.627-0.903 (Janiszewska and BetlejewskaKadela 1993), while in Japan, 4.8 mg/kg on average (Asano et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In the wool of sheep from Greece, Mexico, Poland and Syria, its observed values were from 73.62 to 244.73 mg/kg (Patkowska-Sokoła et al 2009;Ramirez-Perez et al 2000). The Zn content in horses ranged from 19.56 to 860 mg/kg (Asano et al 2002;Janiszewska and Betlejewska-Kadela 1993), and in cattle in an industrialised region from 98.5 to 333.9 mg/g (Rogowska et al 2009).…”
Section: Discussionmentioning
confidence: 99%